1986
DOI: 10.1172/jci112483
|View full text |Cite
|
Sign up to set email alerts
|

Long-term nocturnal calcium infusions can cure rickets and promote normal mineralization in hereditary resistance to 1,25-dihydroxyvitamin D.

Abstract: We report the beneficial effects of calcium infusions in a child with hereditary resistance to 1,25(OH)2D and alopecia. This patient after transient responsiveness to vitamin D derivatives became unresponsive to all therapy despite serum 1,25(OH)2D concentrations maintained at levels -100-fold normal. A 7-mo trial with calcium infusions led to correction of biochemical abnormalities and healing of rickets. Bone biopsies (n = 3) showed a normal mineralization and the disappearance of the osteomalacia. Cultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(88 citation statements)
references
References 34 publications
(24 reference statements)
4
84
0
Order By: Relevance
“…(38,39) Earlier studies in humans with VDDR-II/ HVDRR also had shown that the rachitic phenotype was reversible with calcium treatment. (40) Thus, the present findings of very early developmental expression of the 1␣(OH)ase and VDR in embryonic stem cells and fetal tissues including the developing skeleton are paradoxical. On the one hand, this would suggest an important role for 54 PANDA ET AL.…”
Section: Discussionmentioning
confidence: 67%
“…(38,39) Earlier studies in humans with VDDR-II/ HVDRR also had shown that the rachitic phenotype was reversible with calcium treatment. (40) Thus, the present findings of very early developmental expression of the 1␣(OH)ase and VDR in embryonic stem cells and fetal tissues including the developing skeleton are paradoxical. On the one hand, this would suggest an important role for 54 PANDA ET AL.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, its overall effects on bone formation as well as bone resorption via direct regulation of gene expression are well established [5,20]. That many of these effects of 1,25(OH) 2 D 3 in bone are redundant with other regulatory factors is also well recognized and highlighted most recently by the finding that the dramatic skeletal phenotype observed in the VDR null mouse can be rescued through a diet rich in calcium and phosphorous [21]. It is now believed, however, that high levels of calcium and phosphorus cannot fully normalize the skeletal defects associated with genetic ablation of the VDR or 1,25(OH) 2 D 3 deficiency, manifest as reductions in osteoblast numbers, mineral apposition rate, and bone volume compared to that seen in wildtype mice.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, when vitamin D-deficient rats were fed a high calcium, high phosphorus diet, histological studies of the skeleton did not reveal any skeletal abnormalities consistent with either osteomalacia or rickets (Holtrop et al 1986). When a child with severe rickets caused by the rare hereditary disease VDDR-II (also known as hereditary resistance to 1,25(OH) 2 D), which is caused by loss-of-function mutations in the VDR, was infused with calcium for 7 months, her skeleton began to mineralize normally (Balsan et al 1986). Our recent studies showed that mineralization of both cartilage and bone was severely impaired in the 1a(OH)ase…”
Section: Discussionmentioning
confidence: 99%